Natural background levels of chemical components in groundwater of Hutuo River catchment area, North China Plain. Issue 1 (2nd January 2017) - Zhang, Ying; Chen, Zongyu; Sun, Jichao; Wang, Jincui
ABSTRACT: Natural background levels (NBLs) are commonly used to serve as references when assessing the contamination status of groundwater units. In this study, a methodology based on hydrogeochemistry and statistics was proposed to derive NBLs. A comprehensive understanding of the evolution of groundwater chemistry was acquired and the impact of natural and anthropogenic factors was analyzed based on a total of 93 groundwater samples. The hydrogeochemical plots and the Pau Ta criterion were applied to define the anomalies of the monitoring data by calculating the corresponding Mahalanobis distance. The NBLs were defined for the remaining groundwater samples of the three aquifers after excluding the anomalies with certain percentiles such as median and 90% percentile by means of cumulative frequency plots. Analysis of the hydrochemical data shows that for the aquifers studied, rock weathering dominates the evolution of groundwater chemistry in conjunction with cation exchange, and the dissolution of calcite and silicate weathering are responsible for the major chemical constituents of the groundwater. The NBLs established in the present study showed a difference in groundwater among three aquifers due to the distinct geological conditions. The background of nitrate in the groundwater of the unconfined aquifer was acquired according to the cumulative frequency plot. Deeper insight into the geochemical evolution of groundwater and the establishment of NBLs can be beneficial to improve groundwater management for sustainable development in rapidly urbanizing areas.